Neutron scattering and thermodynamic studies of the magnetic material Yb2Ti2O7 at mK temperatures - Thompson, J (2016)
The frustrated pyrochlore magnet Yb2Ti2O7 has been proposed as a candidate "quantum spin ice" material. This thesis reports extensive inelastic neutron scattering measurements of the spin dynamics and complementary specific heat measurements to map the phase diagram in magnetic fields applied along the cubic [001] direction, not explored experimentally in detail before. The high quality of the single crystals is evidenced by a sharp specific heat anomaly near 215 mK in zero field. In field heat capacity measurements show that the heat capacity peak is completely suppressed by very small magnetic fields (μ0Hint ∼ 0.018 T), and the opening of an excitation gap upon increasing field in the form of a broad hump in the data. Inelastic neutron scattering measurements at the highest magnetic fields probed (9 T), in addition to dominant one-magnon excitations, also show a broad scattering continuum at higher energies, not detected in previous neutron scattering studies, which is attributed to two-magnon excitations. The evolution of the spectrum upon lowering field is characterised in detail, showing how high-energy magnons decay when they overlap with the high-energy continuum (B < 3 T) and the low-energy magnons have their dispersion bandwidth suppressed upon lowering field, and disappear altogether at zero field, where the scattering spectrum consists of a gapless continuum extending over a broad energy range. Through fits of the dispersion relations at high field a re-evaluation of the spin Hamiltonian is proposed to consistently explain quantitatively all existing spin dynamics data for different field directions. A theoretical mean-field calculation indicates that the spin Hamiltonian is very close to a phase boundary line between distinct magnetic orders, and this may be the reason for the unconventional magnetic behaviour, where magnons cannot propagate coherently at any of the energy scales probed.